The Cycle That Brought Me, This Self, and Art Together. (11th November 2022) - Salam, Niga; Jamal, Bzhwen
Abstract : This account details one individual's struggle with the social construction of womanhood in Kurdish society, those roles that females are taught, misogyny and self-hatred that they see deeply imbedded in Kurdish society. Connecting their artwork to their private self, the authors open the space of their personal struggles with gender identification and being queer.